Transformasi Gaya Kepemimpinan dalam Mengelola Tim Remote : Studi Kualitatif Manajer di Perusahaan Startup - Radistha Indah Pratiwi; Husni Awali (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This research aims to understand the process of transformation of leadership styles in managing remote teams in startup companies. Changes in the work environment that increasingly rely on remote work systems encourage leaders to adjust their leadership strategies to remain relevant and effective. Using a qualitative approach and explanatory case study methods, this study explores the experiences of several startup managers who led remote teams through in-depth interviews. The results of this study show that managers experience a process of adaptation in leadership practices that tends to lead to a more open, supportive, and flexible style. The leadership style applied is tailored to the characteristics of the team, work dynamics, and challenges that arise in the context of remote work. These findings reveal that the transformation of leadership styles takes place gradually through a process of reflection and direct experience, which is influenced by personal values and team needs. This research is expected to contribute to the understanding of adaptive leadership practices in the context of digital work, especially in the startup company environment.